Simultaneous occurrence of autoimmune pancreatitis and sclerosing cholangitis as immune-related adverse events of pembrolizumab - Suda, Tsuyoshi (BMJ Case Rep, 2021)
A 57-year-old man with lung cancer, previously treated with the programmed death-1 inhibitor pembrolizumab, was evaluated for liver injury and acute pancreatitis. Serum IgG4 levels were not elevated. Contrast-enhanced CT showed pancreatic swelling, contrast unevenness in the liver and thickening of the common bile duct and gall bladder. Magnetic resonance cholangial pancreatography revealed beads in the left intrahepatic bile duct and localised narrowing of the head and body of the central pancreatic duct. Endoscopic ultrasound-guided fine-needle and liver needle biopsy showed CD8+ and CD4+ T lymphocyte aggregates, whereas immunostaining revealed greater infiltration by CD8+ cells than CD4+ cells. IgG4-related disease was ruled out based on serum and pathological findings. The patient simultaneously presented with immune-related adverse events, autoimmune pancreatitis-like features and sclerosing cholangitis, which were ameliorated by steroid therapy. CD8+ lymphocytes were the dominant infiltrating cells in autoimmune pancreatitis and sclerosing cholangitis.